THE IMPACT OF NEW TECHNOLOGIES ON THE EDUCATION SYSTEM OF UZBEKISTAN (Ustozlar uchun, 2026)
This article examines the impact of new technologies on Uzbekistan's education system. It analyzes opportunities including e-learning platforms, smart classrooms, and AI integration, alongside challenges like digital inequality and teacher training needs. The study presents government initiatives including "Digital Uzbekistan 2030" strategy and recent developments in educational technology, offering recommendations for sustainable integration.